The Predictive Value of PKC and ET-1 Levels in Cerebrospinal Fluid for Vasospasm and Prognosis in Patients with Aneurysmal Subarachnoid Hemorrhage - Li H; Li D; Li M; Hu Z (International Journal of General Medicine)
Hailong Li, Donghua Li, Mi Li, Zehong Hu Department of Neurosurgery, Panzhihua Central Hospital, Panzhihua City, Sichuan Province, People’s Republic of ChinaCorrespondence: Hailong Li, Department of Neurosurgery, Panzhihua Central Hospital, No. 34, Yikang Street, East District, Panzhihua City, Sichuan Province, 617000, People’s Republic of China, Email lihailongdr@21cn.comObjective: To analyze the predictive value of protein kinase C (PKC) and endothelin-1 (ET-1) in cerebrospinal fluid for vasospasm and prognosis in patients with aneurysmal subarachnoid hemorrhage (ASH).Methods: One hundred and forty-eight ASH patients hospitalized in our hospital during February 2019 to February 2022 were optioned as observation subjects. These subjects were graded into good prognosis group (mRS score 0– 2, n = 102) and poor prognosis group (mRS score 3– 6, n = 46) according to the Rankin Revised Scale Score (mRS) after 6 months of follow-up. Cerebrospinal fluid was collected from patients to detect the content of ET-1 and PKC. The prognostic factors were analyzed using multifactorial logistic regression. The predictive value was assessed using receiver operating characteristic (ROC) curve.Results: The patients with poor prognosis had a higher age level and a higher proportion of ≥ 2 aneurysms, aneurysm diameter ≥ 6 mm, cerebral vasospasm, and Hunt-Hess grade ≥III than those with good prognosis (P < 0.05). The patients with poor prognosis had higher content of PKC and ET-1 than those with good prognosis (P < 0.05). Age, aneurysm diameter ≥ 6 mm, cerebral vasospasm, Hunt-Hess classification ≥grade III, PKC and ET-1 were all risk factors related to the prognosis of ASH (P < 0.05). The area under the curve (AUC) of PKC and ET-1 for diagnosing poor prognosis of ASH was 0.803 and 0.720, respectively. The AUC of the combined detection was 0.873 (P < 0.05). Patients with cerebrovascular spasm had higher content of PKC and ET-1 than those without (P < 0.05). The AUC of PKC and ET-1 for diagnosing cerebral vasospasm in ASH was 0.891 and 0.816, respectively, which was 0.932 for combined detection (P < 0.05).Conclusion: The combination of PKC and ET-1 in cerebrospinal fluid had certain value in predicting the poor prognosis of patients with ASH.Keywords: aneurysmal subarachnoid hemorrhage, prognosis, cerebrospinal fluid, PKC, ET-1, diagnosis